Seniors in the Digital Age: Perceptions, Adaptation and Inclusion - Narang, Sunita; Mahajan, Shalu; Marwaha, Preeti; Kaur, Sharanjit; Rani, Gunjan (Transactions on Engineering and Computing Sciences, 2025)
Digital technology has transformed society over the past two decades. Despite numerous advantages, it is still posing challenges for seniors. While some older adults have embraced these changes, others struggle with digital literacy. Bridging this gap is essential to ensure that seniors can fully participate in the rapid digital transformation. This research explores the perceptions of 359 seniors towards digital transformation and evaluates their adaptation levels. Employing an integrated statistical and machine learning framework, the study reveals that seniors widely recognize the use of digital technology across education, entertainment, healthcare, e-commerce, and communication. Their primary online activities include entertainment, payments, and social networking. Seniors emphasize on the provision for basic computer skill training and secure online environment for the improved digital experience. However, the willingness to adapt with digital transformation varies within seniors. Results indicate a statistically significant difference (p<.05) in willingness to enhance technical knowledge across demographic variables viz., age, marital status, area of residence, education level and work profile. Senior citizens are divided into four segments viz., Functional Adopters, Social Adopters, Reluctant Adopters, and Tech-Savvy Pioneers by using K-means clustering algorithm considering their digital adoption. It is recommended to make tailored policies for inclusion of Indian senior citizens in the digital mainstream as per their segment. Literacy programs, infrastructure and community support may play a critical role for the same.